Light-induced synthesis of micron-sized metallic silver in aqueous extract of Rivina humilis L. fruits and its interaction with Corptotermes curvignathus - Salprima Yudha S; Aswin Falahudin; Morina Adfa; Irfan Gustian; Herlina Herlina (Molekul, 2021)
The aqueous extract of Rivina humilis was suitable to reduce silver ions (Ag+) to form micron-sized metallic silver at room temperature and without any addition of external reducing agent or stabilizer compounds. The reduction process was assisted by light, indicated by the colour change of the reaction mixture and supported by the appearance of peak at 455 nm in spectrophotometric analysis when the reaction was carried out under room light. Based on transmission electron microscopy (TEM) analysis, the as-prepared metallic silver was in spherical form. The analysis results using particles size analyzer (PSA) show their particles distribution from micro to nano size (average size was 199 nm). The interaction behaviour of micron-sized metallic silver/extract solution with Corptotermes curvignathus termites shows that the silver gives small additional effects along with the activity of the extract.